The Abstract Book of the International Student Conference on Pediatrics 2024 - Pargaliauskaitė, Julija; Sakalauskaitė , Austėja (Vilnius University Proceedings, 2024)
The International Student Conference on Pediatrics is an annual collaborative effort between Vilnius University Faculty of Medicine Students' Paediatrics Scientific Group and Rīga Stradiņš University Paediatrics Interest Group. This platform enables medical students from both universities to present their scientific work and findings in pediatric research. This year's conference saw the inclusion of students from Ukraine, further enhancing international cooperation. The conference aims to foster collaboration and academic excellence while promoting enduring partnerships in the field of pediatrics. The Abstract Book contains students’ abstract work, providing an overview of the event.
Keywords: Pediatric Research; International Student Conference; Scientific Work